PENGARUH PERBEDAAN JUMLAH HELAI BENANG SULAM DMC TERHADAP HASIL SULAMAN TERAWANG INGGRIS PADA BAHAN KATUN TOBOYO - Putri Ananda; Weni Nelmira (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Embroidery Terawang Inggris, or known as DMC embroidery (Dollfus-Mieg et Compagnie), is one of the captivating white embroidery techniques in textile art. The use of various numbers of thread strands in the embroidery process can affect the quality of the final result. This research aims to determine the influence of different numbers of DMC embroidery thread strands on the results of English terawang embroidery on Toyobo cotton fabric using 1, 2, and 3 thread strands based on stitch density, stitch neatness, and stitch balance. This research uses an experimental method, with the number of samples as panelists being 16 respondents. The sampling technique uses purposive sampling, while the data collection technique uses a questionnaire. Data analysis techniques use descriptive analysis and hypothesis testing using the Friedman test. The research results obtained that Embroidery with 1 thread strand resulted in